Crescimento e produção de alface em diferentes ambientes e níveis de adubação mineral e orgânica - Cavalheiro, Daielly Baritieri (2014)
The experiment was conducted among June and July 2013 in São Miguel do Iguaçu, Paraná, with the intention of provide information about the best environment, doses and sources of fertilization for the production and growth of lettuce cv. Vanda. The experimental design was randomized blocks arrangement with four replicates, the treatments consisted of two rooms, two sources and three levels of fertilization. Regarding production traits were evaluated plant height, plant diameter, number of leaves, stalk length, leaf area, canopy projection, total fresh weight, leaf fresh weight and productivity. Growth analysis was performed based on a weekly collection at 0, 7, 14, 21, 28 and 35 days after transplanting. The total and leaf dry mass and leaf area were used to calculate the specific leaf area, leaf area ratio, relative growth rate, absolute growth rate and net assimilation rate. Data were subjected to analysis of variance and means were compared by Tukey test (p <0.05) for evaluation of production characteristics and evaluation of growth analysis after the data is submitted analysis of variance was performed to regression, generating a response surface. With respect to characteristics specific leaf area, leaf area ratio, net assimilation rate and relative growth rate, only time effect was observed. The accumulation of leaf area, leaf dry weight, total dry mass increased throughout the crop cycle. The absolute growth rate, leaf area, leaf dry weight and total dry mass of the plants showed influences of the environment, sources and fertilization. The protected environment presented more appropriate climatic conditions for the development and production of lettuce cv. Vanda. From the viewpoint of commercial results of productivity obtained indicate that the protected cultivation with the recommended dose of organic fertilizer environment would be the most appropriate for the cultivation of this vegetable